EVALUASI INOVASI PELAYANAN PUBLIK JAKWIR CETEM DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA TEGAL - Annisa Syafaatul Azmi; R Slamet Santoso; Retna Hanani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
Public service innovation is a change in the implementation of services from offline to online by utilizing the sophistication of digital information which has now become a primary need. Therefore, many studies have been conducted on public service innovations in Disdukcapil, but generally only look at the user side so this study aims to analyze how far the success of the Tegal City Disdukcapil in implementing the